Austerity versus pragmatism: a comparison of Latvian and Polish economic policies during the great recession and their consequences ten years later. Issue 4 (2nd October 2019) - Pataccini, Leonardo; Eamets, Raul
ABSTRACT: Despite many initial similarities, Latvia and Poland represent two opposite extremes in terms of practical and theoretical approaches to the economic crisis. The Polish government applied a 'pragmatic' approach to fight the recession, based on expansionary fiscal policies and currency devaluation. Conversely, the Latvian administration opted for the Austerity and internal devaluation strategy. Consequently, the objective of this paper is to analyze, from the perspective of political economy, the strategies chosen for the economic crisis management and their effects in Latvia and Poland, in light of the main EU narratives about its causes and responses. The research contends that the economic performance of both countries during the crisis was due to their respective economic structures. On the one hand, Poland is a bigger, more diversified and industrialized economy, with fewer channels of vulnerability and could apply expansionary policies effectively. On the contrary, the economic model established in Latvia generated a high exposure to external shocks, in particular, with a double vulnerability in the banking sector. In this context, due to internal and external motives, the Latvian government decided to apply the austerity and internal devaluation strategy, worsening the economic decline and the subsequent recovery.